Penyakit Ginjal Kronis pada Anjing dan Kucing: Manajemen Terapi dan Diet - Yanuartono Yanuartono; Alfarisa Nururrozi; Soedarmanto Indarjulianto (Jurnal Sain Veteriner, 2017)
Chronic kidney disease is a progressive impairment of renal function and irreversible. The kidneys fail to maintain metabolism and fluid and electrolyte balance, causing uremia. This disease is a common problem in old cats and dogs that not detected by the owners up to 75 % of kidney function is damaged. Clinical signs vary as polyuria, polidipsi, anorexia, vomiting, weight loss, pale mucous membranes, mouth ulceration, halitosis and acute blindness. Chronic renal failure is not curable so that the necessary medication management and proper diet in orderto improve the quality of life and prolong the life of the animal.